Capacitance sensor for measuring water level - Brayner de Oliveira Lira, Carlos Alberto; Mendes Sobrinho, José Augusto; Dantas Antonino, Antônio Celso; Lobo Vaz de Mello, Fernando; Gusmão Carneiro, Clemente José (Pesquisa Agropecuaria Brasileira, 1997)
A water level sensor, based on a varnished copper wire, was developed. Water and copper are the plates of the capacitor, and the varnish, the dielectric. Nine sensors with wires of different diameters were individually calibrated. For each wire, a linear regression was calculated between the water levels and their respective capacitances. All of the determination coefficients showed values near to the unity. Capacitance of wire ranges from 37.3 to 84.3 pF/cm.